The Urgency of Ecological Intelligence in History Learning: A Literature Review - Yuver Kusnoto; Nana Supriatna; Erlina Wiyanarti; Said Hamid Hasan (Studies in Learning and Teaching, 2023)
This article aims to provide an overview of the importance of planting ecological intelligence for students, especially students in historical learning. The method used in research is the literature review method to see the development of ecological intelligence studies in the educational environment which is focused on historical learning. Literature search is carried out comprehensively and systematically. The results of this study provide a comprehensive description of the urgency of ecological intelligence of students in history learning. So far, ecological intelligence tends to be built for the current interests without paying attention to and studying the relationship between behavior and local wisdom of the community that has been done for a long time for sustainability. Even though events that occurred in the past or today are closely related to the environment that influences human behavior.